2018
DOI: 10.1016/j.cimid.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Immune response biomarkers in human and veterinary research

Abstract: A B S T R A C TBiomarkers are increasingly utilised in biological research and clinical practice for diagnosis of disease, monitoring of therapeutic prognosis, or as end points in clinical studies. Cytokines are small molecules that orchestrate immune responses and as such have great potential as biomarkers for both human and veterinary fields. Given the ease of sampling in the blood, and their high prevalence in clinical applications we will focus on protein detection as an area for biomarker discovery. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…For an accurate interpretation, it must be acknowledged that mRNA expression is not synonymous with protein production (68-70). Accordingly, minor changes in the expression of potent mediators, such as cytokines, can potentially have far-reaching biological effects (71)(72)(73)(74). Conversely, what may be calculated as statistically significant changes in gene expression may produce relatively negligible downstream consequences due to posttranscriptional and post-translational regulatory mechanisms (75,76).…”
Section: Discussionmentioning
confidence: 99%
“…For an accurate interpretation, it must be acknowledged that mRNA expression is not synonymous with protein production (68-70). Accordingly, minor changes in the expression of potent mediators, such as cytokines, can potentially have far-reaching biological effects (71)(72)(73)(74). Conversely, what may be calculated as statistically significant changes in gene expression may produce relatively negligible downstream consequences due to posttranscriptional and post-translational regulatory mechanisms (75,76).…”
Section: Discussionmentioning
confidence: 99%
“…These five cytokines are thus implicated to play an important role in the immune responses against pathogens, defining the Th1/Th2 cytokine responses, and the nature of macrophage activation. These features make cytokines valuable biomarkers to assess the type of immune response induced by, for example, infectious diseases [ 10 ] or act as indicators for cellular activation in in vitro assays [ 11 ]. Therefore, the presence of cytokines in serum, plasma, or supernatant from cultured cells serves as an important biomarker for assessing immune function.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both groups showed trends of gradual increases in IL-6 but no changes in TNF-α: recent studies suggest psychological stress activates the immune system [ 1 , 15 , 29 , 30 ] although inconsistent responses of inflammatory biomarkers across studies have been reported [ 9 , 26 , 31 , 32 ]. These discrepancies in inflammation biomarkers have been explained by: i) the immune response susceptibility to various confounding factors [ 9 , 33 ]; ii) inter-individual differences [ 26 , 34 ]; and iii) inconsistencies in sample collection, storage and measurement protocols [ 26 , 35 ].…”
Section: Introductionmentioning
confidence: 99%